WASTE AREA RISK MITIGATION PT. XYZ USING THE HIRARC METHOD AND BOW TIE ANALYSIS - Prasetyo, Doni; Marodiyah, Inggit (Journal for Technology and Science, 2025)
Objective: At PT. XYZ often experiences several work accidents which result in large losses due to weak existing risk management. Frequent work accidents include employees being crushed by rotting buildings, as well as problems arising from inadequate waste disposal and waste burning which causes smoke to enter the production area and become a big problem for production activities. Method: The method used in this research is HIRARC which is used to determine the highest risk and also Bow Tie Analysis which is used as an appropriate risk mitigation tool. Results: The results of this research show that one of the appropriate mitigation methods is to always wear complete personal protective equipment when working and carry out strict supervision and control of K3. Novelty: One of the long-term recommendations that can be applied to company risk mitigation is the creation of official K3 rules that can be updated regularly.